Minor element profiles through Globorotalia inflata shells from cores GeoB6209-2, GeoB6220-1, GeoB6311-2, GeoB2722-1 and plankton tows MP11 (M133-34-1), MP13 (M133-56-1), MP17 (M133-65-1) - Lukas Jonkers; Akshat Gopalakrishnan; Lea Weßel; Cristiano Mazur Chiessi; Jeroen Groeneveld; Patrick Monien; Douglas O Lessa; Raphael Morard (PANGAEA, 2020)
Measurement were conducted using a NewWave UP193 solid-state laser coupled to a Thermo-Finnigan Element2 HR-ICP-MS at the Department of Geosciences, University of Bremen. Isotope abundances of 25Mg, 27Al, 43Ca, 55Mn, 57Fe and 87Sr in foraminifera shells were determined at an irradiance of 1.3 GW cm-2, a laser pulse rate of 5 Hz and a spot size of 50–100 μm. Plasma power was 1200 W, and Helium (0.7 L min-1) and Argon (0.9 L min-1) were used as sample and make-up gases, respectively. All isotopes were analysed at low resolution with five samples in a 20% mass window and a total dwell time of 25 ms per isotope. Blanks were measured for 30 s prior to ablation and every analysis was followed by a wash out time of at least 60 s to avoid cross-contamination between samples. A glass reference material (NIST610) was measured before every five ablation spots as an external calibration standard using the values of Jochum et al. (2011). To assess data quality, a pressed pellet of MACS-3 carbonate standard powder (n=4) and the USGS reference material BHVO-2G (n=18) were analysed as control standards along with the samples. External precision is better than 3.9%, and accuracy as determined by comparison of our reference material data with the GeoReM database (as of July 2020) is better than 3.4% for all elements except for Mg (7.7%). The 43Ca isotope was used as an internal standard. The files contain raw and despiked element counts, calibration factors and calibrated element/calcium ratios.
In: Jonkers, L et al. (2020): Stable isotopes, counts and raw element data of Globorotalia inflata from sediment cores, Southwest Atlantic [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.922024